Haemoglobin K Woolwich: a study of the family of a homozygote. Issue 3 (June 1980) - Cabannes, R; Amegnizin, P; Sangare, A; Arne, D; Casey, R; Lehmann, H
Abstract : A family is described in which the proband is homozygous and several relatives are heterozygous for Hb K Woolwich (beta 130 [H10] Lys leads to Gln). These people are clinically and haematologically normal. The relationship between the presence of Hb K Woolwich and beta +-thalassaemia is discussed. The distribution of Hb K Woolwich in West Africa is discussed and it is seen to be closely associated with the Akan group.